A porous iron-based lithium supplement and a preparation method thereof
During the synthesis of lithium-ion battery positive electrode lithium supplement agent, fine-grained ferrous hydroxide crystal nuclei are generated using a low pH environment, and the loose porous precursor ferrous hydroxide is synthesized by treating it with thickener and surfactant, and finally, the loose porous precursor ferrous hydroxide is treated. The porous Li5FeO4 lithium supplement agent with high purity and low residual alkali was obtained through three stages of high-temperature sintering, which solved the problems of carbon dioxide generation and small particle density during the synthesis process in the prior art, and achieved the effects of high energy density and long cycle life.
Patent Information
- Application Number
- CN202210809942.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-11
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-07-11
AI Technical Summary
The existing lithium-ion battery positive electrode lithium supplement agent has the problem of high-temperature decomposition in the synthesis process, resulting in an increase in surface residual alkali and limited capacity performance. At the same time, the small density of nano-scale particles is not conducive to the increase of energy density.
The fine-grained ferrous hydroxide crystal nucleus was generated by low pH environment. The loose porous precursor ferrous hydroxide was synthesized by thickening agent and surfactant treatment, and the porous Li5FeO4 supplementation with high purity and low residual alkali was obtained through three stages of high-temperature sintering. Lithium agent.
The obtained porous Li5FeO4 lithium supplement agent has a large specific surface area, which can greatly increase the charging capacity of the battery, improve the energy density and cycle life of the battery.
Smart Images

Figure CN115207348B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium battery positive electrode lithium replenisher, and in particular to a porous iron-based lithium replenisher and a preparation method thereof. Background Art
[0002] At present, the penetration rate of lithium-ion batteries in people's lives is increasing, and the demand for lithium-ion batteries in 3C digital products, power vehicles, etc. is also growing. However, at the same time, the requirements for the energy density and cycle life of lithium-ion batteries in various application fields are also increasing. Especially in the promotion of new energy vehicles, due to the limitation of the energy density of lithium-ion batteries, mileage anxiety has become the biggest bottleneck in the application of new energy vehicles. The lithium-ion battery will be charged for the first time during the formation gradient of the preparation process, and the SEI film formed by the first charge will consume a large amount of active lithium from the positive terminal, thereby reducing the energy density of the battery. At the same time, the positive terminal will cause lattice distortion due to lack of lithium to generate an inert layer, increase the battery impedance and reduce the cycle life. At present, positive electrode lithium supplements can be used to release lithium ions during charging to compensate for the consumption of lithium by the SEI film, thereby increasing the energy density of the battery and increasing the range of new energy vehicles.
[0003] The lithium-rich materials such as Li2NiO2, Li5FeO4, Li2CuO2 and Li2O are commonly used for lithium-ion battery replenishment. Among them, Li5FeO4 is favored for its high capacity and low cost. CN112028126A proposes a method of synthesizing small-particle Li5FeO4 using ferrous oxalate as raw material through mixing lithium source, solvent drying and other processes. However, in the synthesis process, ferrous oxalate is used as raw material, and a large amount of carbon dioxide will be generated during the high-temperature decomposition process. Carbon dioxide is not easy to be discharged in the furnace and will react with the lithium source to increase the residual alkali on the surface of Li5FeO4, affecting its capacity. At the same time, the specific surface area of the lithium-replenishing additive obtained is 0.5-1.7m 2 / g. CN106847527A proposed a "method for preparing nano-scale Li5FeO4 particles", which is suitable for capacitors but not for lithium batteries; because the amount of lithium supplement added to the positive electrode is usually 2%-3%, and the small loose density of nano-scale particles will reduce the compaction density of the pole piece and is not conducive to improving the energy density of the battery. CN112117433A proposed a "method for preparing lithium ferrite", which uses Fe 3+and acidic mixed liquid to obtain iron hydroxide colloid, and then sinter the iron hydroxide colloid with lithium source to obtain lithium ferrite; because iron hydroxide colloid is a colloid, its properties are between liquid and solid states, so its particle size cannot be effectively controlled, resulting in a small specific surface area of lithium ferrite. At the same time, because the colloid cannot be effectively precipitated, if filter pressing is used, it will be lost with the liquid phase during the dehydration stage; if the spray drying method is used to dry the solution, the cost is relatively high, the unit product energy consumption is large, the thermal efficiency and volume heat transfer coefficient are low, and the drying equipment is large in size, complex in structure, and the one-time investment is large. Summary of the invention
[0004] In view of the above problems, the present invention aims to provide a porous iron-based lithium supplement with low cost, large specific surface area, looseness and porosity, and a preparation method thereof.
[0005] To achieve the technical purpose, the present invention provides a porous iron-based lithium supplement, comprising more than 95% by mass of Li5FeO4, a residual alkali rate of less than 5.0%, and a specific surface area of Li5FeO4 of 10-30 m 2 / g.
[0006] A method for preparing a porous iron-based lithium supplement, the specific steps are as follows:
[0007] S1. In a sealed container under the protection of an inert atmosphere, dissolve the ferrous source in deoxygenated deionized water, then add a thickener and stir evenly to obtain Fe 2+ A mixed solution having an ion molar concentration of 0.1-4.0 mol / L;
[0008] S2, adding an alkaline solution to the mixed solution so that the pH value of the mixed solution is between 9 and 11;
[0009] S3, continue stirring until the precipitated particles reach the specified particle size D50: 1-2 μm, then add the surfactant and continue stirring until the particle size reaches D50: 3.5-15 μm;
[0010] S4, filtering and vacuum drying the precipitate to obtain a porous ferrous hydroxide precursor;
[0011] S5, putting the ferrous hydroxide precursor, the lithium source, and the carbon source into a high-speed mixer in proportion and mixing them evenly to obtain a mixture, wherein the lithium source and the ferrous hydroxide precursor are prepared according to a molar ratio of Li:Fe of 5-7, and the carbon source is prepared according to 0.2-3.0% by mass of the ferrous hydroxide precursor;
[0012] S6. The mixed material is placed in a box-type atmosphere furnace and compressed air without carbon dioxide and water is introduced to perform step-by-step sintering to obtain a porous lithium supplement.
[0013] Preferably, the ferrous source in step S1 is one or more of ferrous nitrate, ferrous sulfate, ferrous chloride and ferrous acetate.
[0014] Preferably, the thickener in step S1 is one or more of carboxymethyl cellulose, methyl cellulose, and sodium carboxymethyl cellulose, and the molar concentration of the thickener in the mixed solution in step S1 is 0.1-2 mol / L.
[0015] Preferably, the alkaline solution in step S2 is sodium hydroxide with a molar concentration of 2-6 mol / L or ammonia water with a molar concentration of 0.1-0.7 mol / L.
[0016] Preferably, the surfactant in step S3 is sodium dibutylnaphthalene sulfonate, and the molar concentration of sodium dibutylnaphthalene sulfonate in the mixed solution is 0.1-0.3 mol / L.
[0017] Preferably, the stepped sintering in step S6 is divided into three gradients: the first gradient: sintering temperature 450-650°C, holding time 4-6h; the second gradient: sintering temperature 700-750°C, holding time 5-10h; the third gradient: sintering temperature 780-850°C, holding time 6-10h.
[0018] Preferably, the lithium source in step S5 is one or more of lithium hydroxide, lithium oxide, lithium carbonate, lithium peroxide, lithium chloride and lithium sulfate.
[0019] Preferably, the specific surface area of the porous lithium supplement is 10-30m 2 / g.
[0020] The beneficial effects of the present invention are as follows: the Li5FeO4 porous lithium supplementer prepared by the preparation method of the present application has a large specific surface area, and applying it to the positive electrode of the battery can greatly increase the charging capacity of the battery; since fine-particle ferrous hydroxide crystal nuclei are initially generated in a low pH environment, and then a thickener is used to suspend the ferrous hydroxide crystal nuclei for a long time, and then a surfactant is added to increase the active sites on the surface of the ferrous hydroxide crystal nuclei, a surface disordered growth of crystal dendrites can be obtained to finally synthesize a loose porous precursor ferrous hydroxide. Compared with the conventional method of adding organic additives together with an iron source and a precipitant during precursor synthesis, the present invention also proposes that adding a surfactant to the surface of the crystal nucleus can ensure the purity of the synthetic product while obtaining a precursor ferrous hydroxide with a larger specific surface area; the obtained porous precursor ferrous hydroxide is synthesized by three-stage high-temperature sintering after being matched with lithium, so as to obtain a porous Li5FeO4 lithium supplementer with high purity and low residual alkali. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a comparison diagram between Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0023] A method for preparing a porous iron-based lithium supplement comprises the following specific steps: S1, in a closed container under the protection of an inert atmosphere, dissolving a ferrous source in deoxygenated deionized water, and then adding a thickener and stirring to obtain Fe 2+ The mixed solution has an ion molar concentration of 0.1-4.0 mol / L; the ferrous source is one or more of ferrous nitrate, ferrous sulfate, ferrous chloride, and ferrous acetate. The thickener is one or more of carboxymethyl cellulose, methyl cellulose, and sodium carboxymethyl cellulose. The molar concentration of the thickener in the mixed solution in step S1 is 0.1-2 mol / L.
[0024] S2. Adding an alkaline solution to the mixed solution so that the pH value of the mixed solution is between 9 and 11; the alkaline solution is sodium hydroxide with a molar concentration of 2-6 mol / L and ammonia water with a molar concentration of 0.1-0.7 mol / L.
[0025] S3. Continue stirring until the precipitated particles reach a specified particle size D50: 1-2 μm, then add a surfactant and continue stirring until the precipitated particle size reaches D50: 3.5-15 μm; the surfactant is sodium dibutylnaphthalene sulfonate, and the molar concentration of sodium dibutylnaphthalene sulfonate is 0.1-0.3 mol / L.
[0026] S4, filtering the precipitate and vacuum drying to obtain a porous ferrous hydroxide precursor; the drying temperature is 150-220°C.
[0027] S5. Put the ferrous hydroxide precursor, lithium source and carbon source into a high-speed mixer in proportion and mix them evenly to obtain a mixture, wherein the Li in the lithium source and the Fe in the ferrous hydroxide precursor are mixed in a molar ratio of Li:Fe=5-7, and the carbon source is mixed according to 0.2-3.0% of the mass percentage of the ferrous hydroxide precursor; the lithium source is one or more of lithium hydroxide, lithium oxide, lithium carbonate, lithium peroxide, lithium chloride and lithium sulfate.
[0028] S6. Place the mixture into a box-type atmosphere furnace and introduce compressed air without carbon dioxide and water for step-by-step sintering to obtain a porous lithium supplement. Step-by-step sintering is divided into three gradients: the first gradient: sintering temperature 450-650°C, insulation time 4-6h; the second gradient: sintering temperature 700-750°C, insulation time 5-10h; the third gradient: sintering temperature 780-850°C, insulation time 6-10h.
[0029] The porous iron-based lithium supplement prepared by the above method has a Li5FeO4 content of more than 95% by mass and a residual alkali rate of less than 5.0%, wherein the specific surface area of Li5FeO4 is 10-30m 2 / g.
[0030] Example 1
[0031] Under N2 protection conditions, 20 L of 3 mol / L ferrous sulfate solution was added to a 30 L reactor, and 1 L of 0.2 mol / L carboxymethyl cellulose was added to start stirring to obtain a mixed solution; then 2 mol / L sodium hydroxide solution and 0.3 mol / L ammonia water were added to adjust the pH of the mixed solution to 10.
[0032] When the particle size D50 of the preliminary nucleation ferrous hydroxide precipitate reaches 1 μm, 0.5 L of 0.2 mol / L surfactant sodium dibutylnaphthalene sulfonate is added; stirring is continued until the particle size D50 of the ferrous hydroxide precipitate reaches 3.5 μm. The mixed solution is pumped into a plate-frame filter press to separate the liquid phase to obtain a filter cake, and then the filter cake is vacuum dried in a double cone dryer at 200° C. to obtain a porous ferrous hydroxide precursor.
[0033] The lithium source LiOH and the ferrous hydroxide precursor are prepared in a molar ratio of Li / Fe=5.5, and glucose is added in an amount of 0.25% by weight of the ferrous hydroxide precursor, and the three are put into a high-speed mixer for high-speed mixing. After being evenly mixed, the mixture is put into a box-type closed atmosphere furnace, and compressed air without carbon dioxide and water is introduced. The first gradient sintering temperature is 450° C. and kept for 4 hours; the second gradient sintering temperature is 700° C. and kept for 10 hours; the third gradient sintering temperature is 780° C. and kept for 10 hours, and a porous lithium supplement agent rich in lithium Li5FeO4 is obtained after cooling and crushing;
[0034] Example 2
[0035] Under N2 protection, 15 L of 5 mol / L ferrous sulfate solution was added into a 30 L reactor, 0.8 L of 0.15 mol / L sodium carboxymethyl cellulose was added to start stirring, and then 3 mol / L sodium hydroxide solution and 0.3 mol / L ammonia water were added to adjust the pH to 11.
[0036] When the particle size D50 of the initially nucleated ferrous hydroxide reaches 1.5 μm, 0.6 L of 0.3 mol / L surfactant sodium dibutylnaphthalene sulfonate is added; stirring is continued until the particle size D50 of the ferrous hydroxide particles reaches 5.5 μm, the slurry is pumped into a plate and frame filter press to separate the liquid phase to obtain a filter cake, and then the filter cake is vacuum dried in a double cone dryer at 180° C. to obtain a porous ferrous hydroxide precursor.
[0037] The lithium source Li2CO3 and the ferrous hydroxide precursor are mixed in a molar ratio of Li / Fe=5.8, and glucose accounting for 0.25% of the mass of the ferrous hydroxide precursor is added. The three are loaded into a high-speed mixer for high-speed mixing. After mixing evenly, they are put into a box-type closed atmosphere furnace, and compressed air except carbon dioxide and water is introduced. The first gradient sintering temperature is 550°C and kept for 4 hours; the second gradient sintering temperature is 730°C and kept for 10 hours; the third gradient sintering temperature is 800°C and kept for 10 hours. After cooling and crushing, a porous lithium supplement agent rich in lithium Li5FeO4 is obtained.
[0038] Example 3
[0039] Under N2 protection conditions, 16 L of 4 mol / L ferrous nitrate solution was added to a 30 L reactor, 0.4 L of 0.25 mol / L sodium carboxymethyl cellulose was added to start stirring, and then 2 mol / L sodium hydroxide solution and 0.25 mol / L ammonia water were added to adjust the pH to 11.
[0040] When the particle size D50 of the initially nucleated ferrous hydroxide reaches 2.0 μm, 1.2 L of 0.3 mol / L surfactant sodium dibutylnaphthalenesulfonate is added and stirred continuously until the particle size D50 of the ferrous hydroxide reaches 10.5 μm. The slurry is pumped into a plate and frame filter press to separate the liquid phase to obtain a filter cake, and then the filter cake is vacuum dried in a double cone dryer at 180° C. to obtain a porous ferrous hydroxide precursor.
[0041] The lithium source Li2O and the ferrous hydroxide precursor are prepared in a molar ratio of Li / Fe=5.7, and glucose is added in an amount of 0.25% by weight of the ferrous hydroxide precursor, and the three are loaded into a high-speed mixer for high-speed mixing. After being evenly mixed, the mixture is put into a box-type closed atmosphere furnace, and compressed air except carbon dioxide and water is introduced. The first gradient sintering temperature is 500°C and kept for 4 hours; the second gradient sintering temperature is 700°C and kept for 10 hours; the third gradient sintering temperature is 820°C and kept for 10 hours. After cooling and crushing, a porous lithium supplement agent rich in lithium Li5FeO4 is obtained.
[0042] Comparative Example 1
[0043] Under N2 protection, 16 L of 4 mol / L ferrous nitrate solution was added to a 30 L reactor, and then 2 mol / L sodium hydroxide solution and 0.25 mol / L ammonia water were added to adjust the pH to 12. Stirring was performed until the particle size D50 reached 10.5 μm (comparative example 1 did not add surfactant relative to example 1), the slurry was pumped into a plate and frame filter press to separate the liquid phase, and then the filter cake was vacuum dried in a double cone dryer at 180° C. to obtain a porous ferrous hydroxide precursor.
[0044] The lithium source Li2O and the ferrous hydroxide precursor are prepared in a molar ratio of Li / Fe=5.7, and glucose is added in an amount of 0.25% by weight of the ferrous hydroxide precursor, and the three are loaded into a high-speed mixer for high-speed mixing. After being evenly mixed, the mixture is put into a box-type closed atmosphere furnace, and compressed air except carbon dioxide and water is introduced. The first gradient sintering temperature is 500°C and kept for 4 hours; the second gradient sintering temperature is 700°C and kept for 10 hours; the third gradient sintering temperature is 820°C and kept for 10 hours. After cooling and crushing, a porous lithium supplement agent rich in lithium Li5FeO4 is obtained.
[0045] Table 1 Specific surface area of the embodiments and comparative examples
[0046] Case <![CDATA[Specific surface area (m 2 / g)]]> Example 1 25 Example 2 18 Example 3 15 Comparative Example 1 5
[0047] Combined with Figure 1 , the charging curve of the button battery made of the Li5FeO4 porous lithium supplementer synthesized in Example 1 when charged to 4.3V (the dotted curve corresponding to Example 1), at this time the charging capacity has reached 650mAh / g. However, the charging capacity of the lithium supplementer synthesized in Comparative Example 1 at the same voltage is only 410mAh / g (the continuous curve corresponding to Comparative Example 1). In summary, the Li5FeO4 porous lithium supplementer prepared by the preparation method of the present application has a large specific surface area, and applying it to the positive electrode of the battery can greatly increase the charging capacity of the battery.
[0048] The method of the present application utilizes a low pH environment to initially generate fine-particle ferrous hydroxide crystal nuclei. The addition of a thickener prevents the ferrous hydroxide crystal nuclei from sinking to the bottom, but allows them to suspend in a mixed solution for a long time. A surfactant is then added to increase the active sites on the surface of the ferrous hydroxide crystal nuclei, and crystal dendrites grow disorderly on the surface of the ferrous hydroxide crystal nuclei to eventually synthesize a loose porous precursor ferrous hydroxide. The lithium is then added and sintered at high temperatures in three stages to synthesize porous Li5FeO4. The purpose of the first stage of heat preservation is to decompose ferrous hydroxide into hydroxide and fully oxidize iron to trivalent, the purpose of the second stage of heat preservation is to promote the decomposition of LiOH into Li2O, and the third stage of heat preservation is to oxidize Li + The heavy diffusion migration to the porous precursor provides sufficient activation energy.
[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any slight modification, equivalent substitution and improvement made to the above embodiment based on the technical essence of the present invention should be included in the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a porous iron-based lithium supplement, characterized in that: The specific steps are as follows: S1. In a sealed container under the protection of an inert atmosphere, dissolve the ferrous source in deoxygenated deionized water, then add a thickener and stir evenly to obtain Fe 2+ A mixed solution having an ion molar concentration of 2.0-6.0 mol / L; S2, adding an alkaline solution to the mixed solution so that the pH value of the mixed solution is between 9 and 11; S3, continue stirring the mixed solution until the precipitated particles reach the specified particle size D50: 1-2 μm, then add the surfactant, and continue stirring until the precipitated particle size reaches D50: 3.5-15 μm; S4, filtering and vacuum drying the precipitate to obtain a porous ferrous hydroxide precursor; S5, putting the ferrous hydroxide precursor, the lithium source, and the carbon source into a high-speed mixer in proportion and mixing them evenly to obtain a mixture, wherein the lithium source and the ferrous hydroxide precursor are prepared according to a molar ratio of Li:Fe of 5-7, and the carbon source is prepared according to 0.2-3.0% by mass of the ferrous hydroxide precursor; S6. The mixed material is placed in a box-type atmosphere furnace and compressed air without carbon dioxide and water is introduced to perform step-by-step sintering to obtain a porous lithium supplement.
2. The method for preparing the porous iron-based lithium supplement according to claim 1, characterized in that: In step S1, the ferrous source is one or more of ferrous nitrate, ferrous sulfate, ferrous chloride, and ferrous acetate.
3. The method for preparing the porous iron-based lithium supplement according to claim 1, characterized in that: The thickener in step S1 is one or more of carboxymethyl cellulose, methyl cellulose, and sodium carboxymethyl cellulose, and the molar concentration of the thickener in the mixed solution in step S1 is 0.1-2 mol / L.
4. The method for preparing the porous iron-based lithium supplement according to claim 1, characterized in that: In step S2, the alkaline solution is sodium hydroxide with a molar concentration of 2-6 mol / L and ammonia water with a molar concentration of 0.1-0.7 mol / L.
5. The method for preparing the porous iron-based lithium supplement according to claim 1, characterized in that: The surfactant in step S3 is sodium dibutylnaphthalene sulfonate, and the molar concentration of sodium dibutylnaphthalene sulfonate in the mixed solution is 0.1-0.3 mol / L.
6. The method for preparing the porous iron-based lithium supplement according to claim 1, characterized in that: The step sintering in step S6 is divided into three gradients: the first gradient: sintering temperature 450-650°C, holding time 4-6h; the second gradient: sintering temperature 700-750°C, holding time 5-10h; the third gradient: sintering temperature 780-850°C, holding time 6-10h.
7. The method for preparing the porous iron-based lithium supplement according to claim 1, characterized in that: The lithium source in step S5 is one or more of lithium hydroxide, lithium oxide, lithium carbonate, lithium peroxide, lithium chloride, and lithium sulfate.
8. The method for preparing the porous iron-based lithium supplement according to claim 1, characterized in that: The specific surface area of the porous lithium supplement is 10-30m 2 / g.
Citation Information
Patent Citations
Nanoscale carbon aerogel-Li5FeO4 composite and preparation method thereof, hybrid supercapacitor and preparation method thereof
CN106847527A
Preparation method and application of small-particle-size lithium supplementing additive Li5FeO4
CN112028126A
Preparation method of lithium ferrite
CN112117433A
Modified lithium ion battery positive electrode material as well as preparation method and application thereof
CN114709383A